STRATEGI PENGEMBANGAN MODEL KELEMBAGAAN KEMITRAAN AGRIBISNIS HORTIKULTURA DI BALI - KURNIA SUCI INDRANINGSIH; ASHARI -; SUPENA FRIYATNO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
The role of horticulture commodities is very importance to enhance the growth ofagriculture sector, and its elasticity causes the changing of income. To fill the marketdemand and consumer preference, the constrains related to efficiency, productivity, andquality of horticulture commodities should be attended seriously and to be as priorityefforts. The solution to achieve those conditions is creating the partnership institution thatfarmers and other stakeholders can take benefit for each other and practice a good qualitymanagement. Bali province is one of famous region in Indonesia which has a high-marketdemand on horticulture commodities. The study aim to present identification results ofpartnership pattern, constrain, and it’s potency in Bali. Further, the formulation ofalternative partnership models instead of existing partnership models also will bediscussed. The result showed that generally, partnership pattern have been existing in Balii.e.: plasm-nucleus model, agribusiness operational cooperative, farmers–sub terminalagribusiness (STA) cooperative and reguler trading. The efforts to improve agribusinesspartnership model can be implemented through: (1) developing horticulture farmersassociation, (2) increasing market service information, (3) pushing the role of fieldextension worker, (4) building the vertical communication networking among agribusinessactors, (5) improving the Sub Terminal Agribusiness infrastructure, and (6) empoweringthe financial institution.